The Impact of Probiotic Supplementation on Physical Performance: A Systematic Review of Studies from 2021–2026 - Pociej, Aleksandra Iga; Drobashko, Arina; Murawska, Nikola; Wójcik, Kamil; Kępska, Julia; Kowalczyk, Wiktor; Olech, Weronika; Synakiewicz, Aneta; Lewińska, Natalia (Journal of Education, Health and Sport, 2026)
Background: Physical activity promotes health and positively modulates the gut microbiota. Evidence suggests a "gut-muscle axis" through which probiotic supplementation may enhance athletic performance. Results across direct performance indicators remain inconclusive due to variations in strains and dosages. Aim: This review aims to evaluate studies on the impact of probiotic supplementation on physical performance. Materials and Methods: A systematic literature search was conducted in PubMed and Scopus databases. The search strategy followed PRISMA guidelines. Studies published between 2021 to 2026 were included based on the PICO framework: healthy adults, oral probiotic intervention, placebo control, and validated physical performance outcomes. Results: The analysis indicates that probiotics significantly improve muscular strength, explosive power, and aerobic capacity, particularly when administered as multi-strain formulations or in synergy with other nutrients. Probiotics also effectively attenuate exercise-induced muscle damage, accelerating the recovery. Single-strain interventions and protocols in elite athletes often showed limited effects. High-dose protocols lasting over 8 weeks were the most beneficial. Conclusions: Probiotic supplementation is an effective strategy to support athletic performance and recovery, with its potential significantly amplified through synbiotic combinations. Mechanisms include increased short-chain fatty acid production and reduced oxidative stress and inflammation. Future research must address current limitations, including the lack of female cohorts, small sample sizes, and the need for standardized postbiotic protocols.